Association of Nrf2 expression and mutation with Weiss and Helsinki scores in adrenocortical carcinoma - Kamai, Takao; Murakami, Satoshi; Arai, Kyoko; Ishida, Kazuyuki; Kijima, Toshiki (Cancer science, 2022)
Adrenocortical carcinoma (ACC) is a rare malignant tumor. Genetic abnormalities that may represent therapeutic targets and prognostic factors in ACC remain unclear. Besides being one of the main cellular defense mechanisms that regulates antioxidant pathways for detoxifying reactive oxygen species (ROS), the transcription factor nuclear factor erythroid 2–related factor 2 (Nrf2) promotes tumor proliferation by increasing metabolic activity. In surgical specimens from 12 cases of nonmetastatic ACCs and nine cases of benign adrenocortical adenoma (ACA), we investigated gene mutation and protein expressions for Nrf2 and the preoperative maximum standard glucose uptake (SUVmax) on [18F]fluorodeoxy‐glucose positron emission tomography. Three of five ACCs with a Weiss score of 7 to 9 were Nrf2 mutants; these ACCs had higher expression of Nrf2 and higher preoperative SUVmax. The other seven ACCs had a Weiss score of 3 to 6; these seven ACCs and all the ACAs were non‐Nrf2 gene mutants. Patients with a Weiss score of 7 to 9 and Nrf2 mutant ACC had shorter overall survival. Based on Helsinki scoring, three ACCs with a Helsinki score greater than 17 had Nrf2 mutants, higher expression of Nrf2, higher preoperative SUVmax, and shorter overall survival. Our findings indicate that Nrf2 activation and the associated increase in metabolism play roles in ACC, in particular in ACC with a Weiss score of 7 to 9 and a Helsinki score of greater than 17. Three of five adrenocortical carcinomas with a Weiss score of 7 to 9 were Nrf2 mutants with higher expression of Nrf2, higher glucose uptake in PET, and shorter overall survival, suggesting that activation of Nrf2 and the associated increase in metabolism play roles in the progression of adrenocortical carcinoma.